(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2017)
An experiment was carried out to determine the effect of four different media based hydroponics on plant growth, yield and nutritional values at Biochemistry laboratory of Patuakhali Science and Technology University (PSTU), Bangladesh during November 2014 to April 2015. Tomato plants were grown in closed soilless system where Hoagland solution as nutrient solution and jute fiber, cotton (jhut), coconut husk as substrate. Among four types of media, the media composed with Hoagland solution and jute fiber showed good impact on growth and nutritional values than the other three media (media of Hoagland solution with coconut husk, Hoagland solution with cotton and only Hoagland solution. It was revealed that the highest plant height, yield, vitamin C, fruit protein, fat and fiber content of all were related to media combination of jute fiber and Hoagland solution. Among all the verities, the highest plant height (106 cm), yield (5.3 kg plant-1), fruit Vitamin C content (64.54 mg 100 g-1), fruit protein (17.67 %), fat (5.2%) and fiber (7.9%) content was recorded from Patharkuchi tomato variety. Int. J. Agril. Res. Innov. & Tech. 6 (2): 82-86, December, 2016